On the trail of a brazilian school esthetic in the 1950s journal of Pedagogical Current affairs and school images (2015)
The Journal of Pedagogical Current Affairs, published by the Editorial Nacional from 1950 to 1962 played an important role of dissemination in institutions, ideas, research, legislation, and pedagogical proposals in different areas of education. This paper analyzes the images of school routines in two copies of the Journal of Pedagogical Current Affairs published in 1955 and 1960 with the purpose of pointing how school esthetic was configured in the mentioned decade, in Brazil.Throughout its twelve years of existence, the Journal published images of various educational institutions, mainly high school. It helped build a school esthetic, in Brazil, in the 50s, during the expansion of the education system.Most of the covers contain images of buildings and structures that will be presented in the body of each volume. The selected images of institutions in different spaces such as classrooms, laboratories, playgrounds, offer readers a glimpse of teachers and students in aspects that distinguish them as such.In the analysis of these images, it is evident the place that school took in building relevant social values for a certain period. Some evidence of this attempt to modulate the esthetic and moral awareness is in the representations of the classrooms, uniforms, and in the students practices, in the teachers clothing, in the images of laboratories, and in the science and mathematics classes in which it is possible to identify some traits of modernization of developmentalism and spirit of Brazilian society.From these images, taken as historical sources, we analyze the link between education policy and nationalization associated with values taught by the Brazilian school in the 50s '. In general, it was observed that those images were not able to show “that it could not be" in favor of showing ‘’what should be” or "what we wanted it to be." The reader should be taken to conceive what he wanted it to be the Brazilian school by reading the text and the images. The images that were offered to the reader’s perception operated for the construction of what was intended for school at that time.